The use of electromyogram in football systematic review - Katanic, B.; Ilic, P.; Stojmenovic, A.; Stankovic, M.; Vitasovic, M. (SportLogia, 2022)
The aim of this systematic review was to indicate and discuss the use of electromyogram in football. For the literature review, following electronic databases were used: Google School, PubMed, Medline and Mendeley for the period from 2005. to 2019. 20 papers were selected for this systematic review based on the established criteria. These studies focused the most on researching the following muscles: m.musculus quadriceps, m.biceps femoris, m.gastrocnemius, m.tibalis anterior and m. gluteus maximus. The review has determined quite a heterogenic choice of topics when it comes to the use of the electromyogram (herein after referred to as: EMG) in football, so the obtained results were grouped based on the similar characteristics. Therefore, the results were categorized according to the following topics: acute effects of the specific football activity, impact of the football strength training, training of kicking on the ball, results based on the difference in sexes, while the rest of the results were sorted in the joint group. Summarizing of the obtained results provides the insight in the multiple possibility for use of EMG in football in order to develop high quality analysis of the neuro-muscle activation of a certain muscle regions of the football players.